2017
DOI: 10.1128/aem.00078-17
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 2′-Chloropentostatin and 2′-Amino-2′-Deoxyadenosine Highlights a Single Gene Cluster Responsible for Two Independent Pathways in Actinomadura sp. Strain ATCC 39365

Abstract: 2=-Chloropentostatin (2=-Cl PTN, 2=-chloro-2=-deoxycoformycin) and 2=-amino-2=-deoxyadenosine (2=-amino dA) are two adenosine-derived nucleoside antibiotics coproduced by Actinomadura sp. strain ATCC 39365. 2=-Cl PTN is a potent adenosine deaminase (ADA) inhibitor featuring an intriguing 1,3-diazepine ring, as well as a chlorination at C-2= of ribose, and 2=-amino dA is an adenosine analog showing bioactivity against RNA-type virus infection. However, the biosynthetic logic of them has remained poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…It is believed that 8 and 10 may share the same precursor, possibly from the primary metabolite pathway. The semi‐purified fractions containing 8 , 9 , and 10 were subjected to the analysis of high‐resolution mass spectrometry (HRMS) with the mass‐to‐charge ratio ( m / z ) of 303.0837, 269.1244, and 267.1168, respectively, fully consistent with the previous results …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is believed that 8 and 10 may share the same precursor, possibly from the primary metabolite pathway. The semi‐purified fractions containing 8 , 9 , and 10 were subjected to the analysis of high‐resolution mass spectrometry (HRMS) with the mass‐to‐charge ratio ( m / z ) of 303.0837, 269.1244, and 267.1168, respectively, fully consistent with the previous results …”
Section: Resultssupporting
confidence: 84%
“…Previous work by Gao et al . revealed that the adechlorin biosynthetic gene cluster ( ade BGC) was composed of 13 genes ( ade A‐ ade M), but none of these were identified to encode the required chlorinase (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…FOR-A and COF were formerly reported to be co-produced by the actinobacteria, Nocardia interforma ATCC 21072 and S. kaniharaensis ATCC 21070 (7, 10), implicating that the genes for their biosyntheses, as those of other purine nucleoside antibiotic pairs, should also constitute a gene cluster (11, 12), Additionally, COF and PTN, featuring significant structural resemblance, were recently revealed to share highly-similar biosynthetic pathways (20).…”
Section: Resultsmentioning
confidence: 99%
“…This intriguing co-biosynthetic phenomenon was also documented for other purine nucleoside antibiotics pairs, including pentostatin (PTN) and arabinofuranosyl adenine (Ara-A) (produced by Streptomyces antibioticus NRRL 3238) (11), 2’-Cl PTN and 2’-amino-2’-deoxyadenosine (produced by Actinomadura sp. ATCC 39365) (12), and fungus-produced PTN and cordycepin (13), which all employ an unusual but general protector-protégé strategy, i.e. PTN may protect Ara-A (taking this antibiotic-pair as example) from deamination by the housekeeping adenosine deaminase (1113).…”
Section: Introductionmentioning
confidence: 99%
“…strain ATCC 39365) ( Fig. 1A) (11), as well as by the fungus-derived PTN and cordycepin pair (produced by Cordyceps militaris and other fungal strains) (12). In addition, we have previously shown that a short-chain dehydrogenase and a SAICAR (phosphoribosylaminoimidazolesuccinocarboxamide) synthetase are highly conserved for the biosynthesis of the heterocyclic 1,3-diazepine ring of the PTN-related compounds (8).…”
mentioning
confidence: 96%